REGARD COMPARATIF SUR LES ENQUÊTES DIALECTALES ROUMAINES : DES "QUESTIONNAIRES DU MUSÉE DE LA LANGUE ROUMAINE À L’ALR I" ET À L’"ALRR – TRANSYLVANIE" - COLCIAR, Rozalia (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Comparative Examination of the Romanian Dialectal Inquiries: from the Questionnaires of the Romanian Language Museum to ALR I and ALRR ‒ Transylvania. Our work approaches, from a comparative point of view, the answers collected as a result of the correspondence linguistic inquiries for Chestionarul II. Casa (Questionnaire II. The Household) elaborated by the Romanian Language Museum in 1926 and the answers referring to the household in the direct inquiries for ALR I and ALRR‒Transylvania. The source data are represented by the material archived at “Sextil Pușcariu” Institute of Linguistics and Literary History of the Romanian Academy ‒ the answers for Questionnaire II. The Household, the unpublished material of ALR I, and the material published in volume III of the Romanian Regional Linguistic Atlas – Transylvania (ALRR‒Transylvania). We selected the material from five localities in Transylvania, common in the three surveys. Analysing the answers for questions onomasiologically documented, first of all, and sometimes semasiologically, we concluded that the answers mostly coincide in the three surveys, the differences being given by the extralinguistic reality. Actually, the temporal distance between the inquiries was not too large and the extralinguistic reality, consequently the area of material life in question, did not suffer major mutations during the investigated period of time. Thus, the study confirms the fact that the linguistic atlases represent genuine language documents, which registered not only the diatopic variation of Romanian language, but also the expressive competence of the speaker as the bearer of a social-historical tradition. REZUMAT. Privire comparativă asupra anchetelor dialectale românești: de la Chestionarele Muzeului Limbii Române la ALR I și ALRR – Transilvania. Lucrarea noastră urmărește, din perspectivă comparativă, răspunsurile obținute în cadrul anchetelor lingvistice prin corespondență pentru Chestionarul II. Casa, elaborat de Muzeul Limbii Române, în 1926, precum și răspunsurile referitoare la acest domeniu din cadrul anchetelor directe efectuate pentru ALR I și ALRR Transilvania. A fost utilizat materialul aflat în arhiva Institutului de Lingvistică și Istorie Literară „Sextil Pușcariu” al Academiei Române, Filiala Cluj-Napoca (pentru răspunsurile la Chestionarul Casa și materialul nepublicat din ALR I), precum și materialul din volumul III al Atlasului Lingvistic Român pe Regiuni. Transilvania. S-au avut în vedere cinci localități din Transilvania, comune celor trei anchete. Analizând răspunsurile obținute pentru chestiuni documentate în primul rând onomasiologic, dar și semasiologic uneori, s-a constatat că, în cea mai mare parte, aceste răspunsuri coincid, diferențele fiind date de realitatea extralingvistică. De altfel, distanța temporală între anchete nu a fost atât de mare, iar realitatea extralingvistică, respectiv domeniul vieții materiale pus în discuție nu a suferit mutații majore în acest interval de timp. Se confirmă, și cu ocazia acestui studiu, faptul că atlasele lingvistice reprezintă adevărate documente de limbă, care înregistrează nu numai variația diatopică a limbii române, ci și competența expresivă a vorbitorului, ca purtător al unei anumite tradiții socioistorice. Cuvinte-cheie: chestionar lingvistic, anchetă prin corespondență, anchetă directă, atlas lingvistic, onomasiologie, semasiologie.